Răspuns :
[12+11:(3/4+1/6)]x7/27=
[12+11: (3x3+2x1/12)]x7/27=
(12+11 : 11/12)x7/12=
(12+11x12/11)x7/12=
(12+12)x7x12=
24x7/12=
2x7=14
[12+11: (3x3+2x1/12)]x7/27=
(12+11 : 11/12)x7/12=
(12+11x12/11)x7/12=
(12+12)x7x12=
24x7/12=
2x7=14
[12+11:(3/ 4 +1/ 6) ] • 7 / 27
=[12+11:(18/ 24 +4/ 24) ] • 7 / 27
=
= (12+11: 22/24 ) • 7 / 27=(12+11*24 / 22 ) • 7 / 27=(12+24/2 ) • 7 / 27=
= (12+12 ) • 7 / 27= 24 *7/ 27= 168/ 27= 56/9
= (12+11: 22/24 ) • 7 / 27=(12+11*24 / 22 ) • 7 / 27=(12+24/2 ) • 7 / 27=
= (12+12 ) • 7 / 27= 24 *7/ 27= 168/ 27= 56/9